Adapting Melanogenesis to a Regioselective C–H Functionalization of Phenols - Esguerra, Kenneth Virgel N.; Lumb, Jean-Philip (Synlett, 2015)
The importance of aromatic carbon–heteroatom bonds to the function of natural products, electronic materials, and pharmaceutically active compounds motivates considerable effort to improve the efficiency of constructing these bonds. Melanogenesis, which is a ubiquitous process by which organisms produce pigments, generates functional materials with high heteroatom content from simple phenolic precursors at the sole expense of reducing molecular oxygen to water. This article outlines our efforts towards the development of a tyrosinase mimic for the aerobic oxygenation of phenols that were inspired by melanogenesis, and highlights its potential to functionalize multiple aromatic C–H bonds in a single operation.
Keywords: biomimetic catalysis; aerobic oxidation; phenols; dearomatization; enzymes; C–H functionalization; copper